The legend of Zelda and philosophy I link therefore I am - Cuddy, Luke 1980- (Peru, Illinois Open Court Publishing Company, 2008)
"Chapters address philosophical aspects of the video game The Legend of Zelda and video game culture in general"--Provided by publisher.
Setting up the game / Luke Cuddy -- Level 1: Emotion, experience, and thought -- Why do we care whether link saves the princess? / Jonathan Frome -- Look before you warp / Douglas Wilson -- Legend and logic : critical thinking in the gaming and real worlds / Robert Arp and Dennis Milarker -- Level 2: Dodongo and death -- Link's search for meaning / Toni Fellela -- The hero with a thousand hearts : death in Zelda / Anna B. Janssen -- Level 3: Don't get manhandled by manhandla-or ... mind-handled? -- Slave morality and master swords : Ludus and Paidia in Zelda / Kristina Drzaic and Peter Rauch -- Shape shifting and time traveling : link's identity issues / Rachel Robison -- Level 4: The CDI games don't count! : timelines and Miyamoto -- The hero of timelines / Sean C. Duncan and James Paul Gee -- Linking to the past : Zelda is a communication game / Carl Matthew Johnson -- Level 5: Time and space in hyrule -- Three days in termina : Zelda and temporality / Lee Sherlock -- Constructing nespace in Zelda / Joaquin Siabra-Fraile -- Level 6: Treasures of the hyrulopolis -- Zelda as art / Luke Cuddy -- Hyrule's green and pleasant land : the minish cap as utopian ideal / Paul Brown -- Level 7: You are nearing the end of your quest ... grumble, grumble -- I am link's transcendental will : freedom from hyrule to earth / Dario S. Compagno -- Zeldathustra / Michael Bruce -- Level 8: The triforce-need I say more? -- A link to the triforce : Miyamoto, Lacan, and you / Patrick Dugan -- The triforce and the doctrine of the mean / Charles Joshua Horn -- Level 9: Don't patra-nize me! -- How can there be evil in hyrule? / Dwayne Collins -- The legend of feminism / Joyce C. Havstad and Iris M. Jahng -- It's a secret to everybody -- Getting to know the world next door / Roger Ngim
Includes bibliographical references and index.
Keywords: Legend of Zelda (Game); Video games -- Philosophy